Keeping obesity status is a risk factor of hypertension onset: evidence from a community-based longitudinal cohort study in North China - Cai, Qiujing; Zhao, Xiaolei; Dong, Liguang; Zhang, Xinmin; Wang, Chenglong; Wang, Shu; Zhou, Yi; Zhou, Xianliang; Li, Yanqi; Wang, Shuyu; Liu, Lisheng; Hu, Aihua (Frontiers in Public Health, 2023)
Objective The purpose of our study was to investigate the association of obesity status change with hypertension onset based on a community-based longitudinal cohort study in North China. Methods This longitudinal study included 3,581 individuals free of hypertension at baseline in the first survey (2011–2012). All participants were followed up (2018–2019). According to the criteria, a total of 2,618 individuals were collected for analysis. We used adjusted Cox regression models and Kaplan–Meier survival analysis to estimate the association between obesity status change and hypertension onset. Additionally, we applied the forest plot to visualize the subgroup analysis including age, gender, and the differences in some variables between baseline and follow-up. Finally, we conducted a sensitivity analysis to examine the stability of our results. Results Over nearly 7 years of follow-up, a total of 811 (31%) developed hypertension. The new hypertension incidence was mostly observed in those who were obese all the time (P for trend < 0.01). In the fully adjusted Cox regression model, being obese all the time increased the risk of hypertension by 30.10% [HR 4.01 (95% CI 2.20–7.32)]. The Kaplan–Meier survival analysis revealed the change in obesity status as an important feature to predict the occurrence of hypertension. Sensitivity analysis shows a consistent trend between the change in obesity status and hypertension onset in all populations. Subgroup analysis showed that age above 60 years was an important risk factor for hypertension onset, that men were more likely than women to develop hypertension, and that weight control was beneficial in avoiding future hypertension in women. There were statistically significant differences in ΔBMI, ΔSBP, ΔDBP, and ΔbaPWV between the four groups, and all variables, except baPWV changes, increased the risk of future hypertension. Conclusion Our study shows that obese status was notably associated with a significant risk of hypertension onset among the Chinese community-based cohort.